Global crime governance off the eastern Africa littoral: does the response to piracy in the Western Indian Ocean provide a model? - Bruwer, Carina (Department of Public Law, 2022)
The transnational character of contemporary organized crime has resulted in cooperative efforts to address crimes which pose a mutual threat to multiple entities across the globe. But are such collective efforts achieving their aims? One such partnership, or group of partnerships, which has, is the global response to Somali piracy in the Western Indian Ocean off eastern Africa. While it has not eradicated piracy or the conditions giving rise thereto, it has effectively contained attacks. This achievement, and the public-private partnerships which gave effect to these efforts, is unprecedented for a response to transnational organized crime at sea. This has sparked debate regarding the response's utility for other transnational organized crimes which continue to plague the world's oceans. Although counter-piracy has been the object of much research due to its international nature, cooperative responses to other forms of transnational organized crime off the eastern Africa littoral have been neglected. In particular, the utility of counter-piracy for these other organized crimes is under-examined. This thesis therefore aims to present evidence to answer the research question: does the global governance response to Somali piracy provide a model for responding to other forms of transnational organized crime in the Western Indian Ocean? The research straddles criminology and law and is grounded in the theoretical frameworks of global governance, organized crime and maritime security. Research data was generated through a literature review, complimented by expert interviews and participant observation. This thesis uses the case studies of heroin and ivory trafficking in the Western Indian Ocean to consider comparative lessons from counter-piracy. It considers each crime's modus operandi, applicable international legal frameworks, impact, responding actors and existing and potential responses. It does so in order to illuminate the conditions under which global governance efforts against transnational organized crime at sea are likely to emerge and achieve success. The responses to piracy, heroin and ivory trafficking are considered at the hand of five paradigms, originally applied to counter-piracy responses by Prof. Christian Bueger. Each paradigm problematizes different aspects of each crime and discusses the resulting responses. The paradigms are categorized as the security, legal, economic, development and humanitarian paradigms. The findings suggest that global crime governance efforts are perhaps more at home at sea than on land and that different crimes mobilize responding actors to enter the maritime domain for different reasons. In addition to threatening national interests, states and other entities responding to maritime crimes are equally influenced by other factors, including corruption, modus operandi, strategic interests, international legal frameworks and human rights concerns. These factors also influence their chosen responses. Significantly, the research found that the private actors integral to counter-piracy are absent in the response to heroin and ivory trafficking, leaving a lacuna which, if not filled, will continue to facilitate the use of the oceans for illicit means. It is concluded that although counter-piracy holds many valuable lessons for global crime governance at sea, a response mimicking counter-piracy is unlikely to form in efforts to counter other forms of transnational organized crimes in the Western Indian Ocean.